On the Measurement of the Absolute Viscosity of Nitrogen and Air Over the Temperature Range of 100 to 400°K and at Pressures of 1 to 150 Atmospheres - Saunders, Michael William (My University, 1972)
A series capillary viscometer has been used to measure the viscosity of nitrogen and air over a temperature range of 100 to 400°K and to pressures of 150 atmospheres.
The low pressure results have been correlated using a modified Sutherland equation of the form: n = C1T^C2 / T+C3
Intermolecular force constants have been computed for nitrogen using the Chapman Enskog collision theory approach.
The viscosity in the dense gas region was correlated using equations of the form n-no = A1ρ + A2ρ^2 and thus overall equations for viscosity as a function of temperature and density were formulated as n = C1T^C2 / T+C3 +A1ρ + A2ρ^2
These equations were used to generate tables of smoothed values of viscosity as a function of pressure and temperature.
Keywords: measurement, absolute viscosity, nitrogen, air, temperature range, pressures, atmospheres